Sueño : new poems - Cervantes, Lorna Dee (Wings Press, 2013)
"Sueño, the fifth major collection by iconic Chicana-Native American poet Lorna Dee Cervantes is intellectually brilliant, linguistically playful, politically intense, and sensually aflame. These poems engage the reader on half a dozen levels at once. If anything, Sueño eexceeds Lorna Dee's reputation for power, insight and word play."--Cover.